The effectiveness of alternative coaching approaches on the confidence of coaches with postgraduate qualifications - Mashele, Amukelani Bertha (My University, 2021)
South Africa is the largest provider of coaches in Africa and fifth largest in the world. It is important that coaches produced in the country are confident in their coaching skills. The purpose of this study was to explore the effectiveness of one-on-one coaching, peer coaching and coaching supervision in improving the confidence of postgraduate coaches at an academic institution in South Africa. The three coaching approaches were explored under the social cognitive, transformative and experiential learning theories. This research was cross-sectional; it identified with a social constructivism worldview following an interpretive approach which used a qualitative method to explore, in-depth, the different subjective understandings held by the participants. Primary data was sourced in the form of semi-structured interviews with 12 postgraduate coaches who had graduated from a coaching programme. A thematic analysis process was employed to analyse the data. It uncovered four main themes with 18 sub-themes. The key findings indicated that all three coaching approaches had different learnings that could be incorporated with the learning theories of Bandura’s social cognitive, Mezirow’s transformative learning and Kolb’s experiential learning. However, coaching supervision was perceived to be the most effective coaching approach in improving the confidence of postgraduate coaches. All three coaching approaches have value to offer for different conditions. Academic institutions offering coaching programmes should continue to invest more resources towards coaching supervision in order to enhance the confidence of postgraduate coaches, not disregarding, however, that practice makes perfect
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in Business and Executive Coaching), 2021
Keywords: Coaching effectiveness; Confidence; One-on-one coaching; Peer coaching; Coaching supervision; Learning theory; SDG-8: Decent work and economic growth